İş Sözleşmesinin İşçi ve İşveren Sıfatının Birleşmesiyle Sona Ermesi - (:unkn) unknown (My University, 2017)
Alacaklı ve borçlu sıfatının aynı kişide birleşmesiyle borç sona erer. İşçi ve işveren sıfatının aynı kişide birleşebileceği unutulmamalıdır. Alacaklı ve borçlu sıfatının birleşmesine ilişkin yasal düzenleme, işçi ve işveren sıfatının birleşmesine de uygulanacaktır. Dolayısıyla işçi ve işveren sıfatı, kendiliğinden veya işyerinin ya da ciddi bir şirket payının işçiye devri gibi bir hukuki işlemle birleştiğinde iş sözleşmesi sona erer. İş yasaları kıdem tazminatının ödeneceği halleri sınırlı olarak saydığından, işçi böyle bir durumda kıdem tazminatına hak kazanamaz.

An obligation is deemed extinguished by merger where the capacities of creditor and debtor are united in the same entity. One should bear in mind that the capacities of employee and employer may unite in the same entity. The regulation regarding the merger of the capacities of the creditor and the debtor shall apply to the merger of the capacities of the employee and the employer. Hence the employment contract comes to an end when the capacities of contractants merge either automatically or by means of a legal transaction such as the transfer of the entreprise or the transfer of a substantial share of the company to an employee. In this case the employee cannot claim any severance pay since the labour legislation enumerates the terms and the conditions in a restrictive manner under which the severance pay shall be paid.
The Dissolution of the Employment Contract by Merger of the Capacities of Employee and Employer
Keywords: Hukuk